A REVIEW ON WIRELESS NETWORK AND ELECTRONIC COMMUNICATION - Prakash, A.; Babu, T.G. (IJRDO -Journal of Computer Science Engineering, 2023)
This file gives an outline of WI-FI networking and descriptions what’s required to construct a general-motive WI-FI community. The literature tries to talk about the maximum not unusual place WI-FI technology and their protocols. It then outlines the benefits of WI-FI networking over stressed era. The white paper additionally addresses a number of the essential protection dangers going through WI-FI networks. Various techniques are for the reason that may be used to mitigate those dangers and guard community privateness and protection. It then outlines how WI-FI networks may be utilized in training and schooling, and suggests that training has benefited from the improvement of WI-FI era and the era’s price-effectiveness.